PENGARUH MODEL CO-OP CO-OP MANDIRI TERHADAP KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI GAYA BELAJAR SISWA - Henri Henri; syamsurizal syamsurizal; syaiful syaiful (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This experimental quasi is aimed to know the influence of Co-op Co-op model independently on problem solving abilities in terms of student learning style. This research method is a quasy experiment with quantitative approach. The subjects of the study were the students of class X IPS 3 and Class X IPS 4. Subject take technique done by perposive sampling. The experimental class used the co-op self-co-op learning model and the control class using the conventional co-op co-op learning model. Data were collected using written test techniques to obtain data on problem solving abilities and student learning styles. Data analysis techniques in hypothesis testing using two away anava, followed by tukey test. The results of this study obtained the average value of experimental class 1 taught with Co-op self-co-op learning model is 65.56, the average experiment class 2 is 66.33 and the average control class that is taught by the model of learning Co-op conventional co-op is 59.83. Based on the result of the research, it can be concluded that (1) There is influence of independent co-op co-op model and learning style to problem solving ability, (2) Co-op Co-op model independent of problem solving ability, (3) learning styles on problem-solving skills and (4) there is an interaction between Co-op co-op models and learning styles in influencing problem-solving abilities.